Monoclonal antibodies in breast cancer: A critical appraisal. (March 2023) - Behl, Akanksha; Wani, Zahoor A.; Das, Nagendra Nath; Parmar, Virinder S.; Len, Christophe; Malhotra, Shashwat; Chhillar, Anil K.
Abstract: In breast cancer, mAbs can play multifunctional roles like targeting cancer cells, sometimes directly attacking them, helping in locating and delivering therapeutic drugs to targets, inhibiting cell growth and blocking immune system inhibitors, etc. Monoclonal antibodies are also one of the important successful treatment strategies especially against HER2 but they have not been explored much for other types of breast cancers especially in triple negative breast cancers. Monoclonal antibodies impact the feasibility of antigen specificity, bispecific and trispecific mAbs have opened new doors for more targeted specific efficacy. Monoclonal antibodies can be used diversly and with efficacy as compared to other methods of treatment thus maining it a suitable candidate for breast cancer treatment. However, mAbs treatment also causes various side effects such as fever, trembling, fatigue, headache and muscle pain, nausea/vomiting, difficulty in breathing, rashes and bleeding. Understanding the pros and cons of this strategy, we have explored in this review, the current and future potential capabilities of monoclonal antibodies with respect to diagnosis and treatment of breast cancer. Data availability: Not applicable Graphical Abstract: ga1 Highlights: Multifunctional role of mAbs. mAbs interaction with breast cancer cells. With many prosmAbs have some adverse effects.